The effect of green channel for stroke patients on treatment of severe aneurysmal subarachnoid hemorrhage - Xue-Jiao Wang; Yu Deng; Xiao-Qing Li; Feng-Feng Jiang; Wen-Yan Jia; He-Chun Zhang; Feng-Ying Chen; Bai-Yun Liu (Chinese Journal of Traumatology)
Purpose: To explore the effect of green channel for stroke patients on the treatment of severe aneurysmal subarachnoid hemorrhage. Methods: This is a retrospective case-control study. The clinical data of patients with severe aneurysmal subarachnoid hemorrhage admitted to the emergency department of our hospital from January 2015 to June 2022 were retrospectively analyzed. Patients diagnosed with subarachnoid hemorrhage, confirmed intracranial aneurysm by preoperative CT angiography or digital subtraction, graded Hunt-Hess grade III, IV, and V, < 72 h from the onset to the time of consultation received surgical treatment in our hospital were included in this study. Patients with serious underlying diseases, such as heart, liver, kidney diseases, or malignant tumors, traumatic subarachnoid hemorrhage, previous history of cerebral hemorrhage, and incomplete data were excluded. The control group included patients with severe aneurysmal subarachnoid hemorrhage admitted from January 2015 to December 2018 before the establishment of the green channel for stroke patients, and the observation group included patients with severe aneurysmal subarachnoid hemorrhage admitted from January 2019 to June 2022 after the establishment of the green channel. The control group received routine treatment in the emergency department; the observation group received improved treatment of green channel for stroke patients. Gender, age, Hunt-Hess grade on admission, modified Rankin scale (mRS) on admission, aneurysm location, aneurysm size and whether accompanied by intracerebral hemorrhage, the time from onset to emergency department, the time from emergency department to vascular diagnostic examination, the time from onset to surgery, the time from emergency department to surgery, the time from hospital admission to surgery, length of hospital stay, complications, treatment effect were analyzed and compared between the 2 groups. SPSS 23.0 software was utilized to conduct comparisons between the 2 groups. The t-test, Chi-square test, or Mann-Whitney U test was chosen based on the data type. Statistical significance was established when p < 0.05. Results: A total of 71 patients were included in this study, of whom 37 were in the control group and 34 were in the observation group. There were no statistical differences in age, gender, Hunt-Hess grade, mRS scores, aneurysm location, aneurysm size, intracerebral hemorrhage, the time from onset to emergency department, length of hospital stay, complications between the observation group and the control group (all p > 0.05). The time (min) from visit to vascular diagnostic test (60.50 vs. 120.00, p = 0.027), the time (min) from onset to surgery (1792.00 vs. 2868.00, p = 0.023), the time (min) from emergency department to surgery (1568.50 vs. 2778.00, p = 0.016), the time (min) from hospital admission to surgery (1188.50 vs. 2708.00, p = 0.043), all of them were shorter in the observation group than those in the control group. The relative values of admission and 7-day postoperative mRS scores and the relative values of admission and discharge mRS scores ≥ 2 were used as the criteria for determining better efficacy, and the treatment effect was better than that in the control group, and the differences were statistically significant (admission to 7 days postoperative mRS score ≥ 2, 17 (50.0 %) vs. 8 (21.6 %), p = 0.012; admission to discharge mRS score ≥ 2, 19 (55.9 %) vs. 11 (29.7 %), p = 0.026). Conclusion: The green channel for stroke patients with severe aneurysmal subarachnoid hemorrhage can effectively shorten the time from arrival at the emergency department to vascular diagnostic examination and the time from the emergency department to surgery, and achieve a better therapeutic effect, which is worth popularizing and applying.